2012
DOI: 10.5194/bgd-9-11925-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concentrations and fluxes of dissolved organic carbon in runoff from a forested catchment: insights from high frequency measurements

Abstract: Concentrations of dissolved organic carbon (DOC) in runoff from catchments are often subject to substantial short term variations. The aim of this study was to identify the spatial sources of DOC and the causes for short term variations in runoff from a forested catchment. Furthermore, we investigated the implication of short term variations for the calculation of annual runoff fluxes. High frequency measurements (30 min intervals) of DOC in runoff, of discharge and groundwater table were conducted for on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…The high DOC concentrations during stormflow are related to near-surface runoff in the organic-rich upper soil layers (Lischeid et al, 2007;Strohmeier et al, 2012). In addition, some of the DOC may also be released from the deeper, anoxic layers due to reductive dissolution of iron (oxy)hydroxides and the release of associated DOC (Zak and Gelbrecht, 2007;Knorr, 2012), and due to desorption of DOC from soil minerals due to the pH increase during reducing conditions (Grybos et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The high DOC concentrations during stormflow are related to near-surface runoff in the organic-rich upper soil layers (Lischeid et al, 2007;Strohmeier et al, 2012). In addition, some of the DOC may also be released from the deeper, anoxic layers due to reductive dissolution of iron (oxy)hydroxides and the release of associated DOC (Zak and Gelbrecht, 2007;Knorr, 2012), and due to desorption of DOC from soil minerals due to the pH increase during reducing conditions (Grybos et al, 2009).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, previous investigations have shown that NOM mobilization from riparian wetland soils into stream water is affected by season and by hydrological conditions (Strohmeier et al, 2012;Jirsa et al, 2013). Temporal variations in NOM export are a direct consequence of the composition of the hydraulically active layers in the soil profile and their respective discharge patterns (Knorr, 2012;Strohmeier et al, 2012). It has been suggested that future changes in the hydrological regime will influence the dynamics of NOM export (Strohmeier et al, 2012), which might in turn influence the dynamics of iron and arsenic export.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…high concentrations of dissolved oxygen or nitrate in deep and very old groundwater (e.g. Strohmeier et al, 2013 or Bartsch et al, 2014) clearly proof, that transformation efficiencies for nitrate can't be very high.…”
Section: Introductionmentioning
confidence: 97%